Shareholders activism and shareholders power to instruct - Mohd. Sulaiman, Aiman @ Nariman (2016)
Objective: An important measure of shareholder primacy and activism is the power to initiate and approve proposals. However, in many countries which have transplanted or inherited the Anglo-Saxon governance model represented by the UK, shareholders intending to present their proposals to the general meeting often face a significant legal barrier due to the division of power doctrine. The article examines recent decisions within the Commonwealth where attempts have been made to reconfigure the division of power doctrine which functions to confer to the board the power to decide on management matters. Method: The article examines the position in several Commonwealth countries regarding director primacy. Result: : This article provides guidance to directors and investors in navigating the limits of the legal framework regarding the power to instruct and offers insights to policy makers interested in enhancing shareholders empowerment.